Knowledge, Attitudes, And Practices Among Caregivers of Children With Β-Thalassemia Major: A Cross-Sectional Study - Parmar, Alpesh; Pandor, Jyotsna; Ninama, Kartik; Talati, Vishwa; Sutaria, Rahi; Nanavati, Savan (Journal of Neonatal Surgery, 2025)
Background: β-thalassemia major (BTM) is a severe inherited blood disorder requiring lifelong blood transfusions and comprehensive disease management. In India, high rates of consanguinity and inadequate premarital screening contribute to the persistent burden of thalassemia. Caregivers' knowledge, attitudes, and practices (KAP) are pivotal in shaping preventive behaviours and long-term outcomes. Objective: To assess the knowledge, attitudes, and practices of caregivers of children with β-thalassemia major and identify gaps that may inform future community-based prevention strategies. Methods: A cross-sectional, observational study was conducted at a tertiary care thalassemia clinic and through community-based home visits. Using a pre-validated, semi-structured questionnaire, data were collected from 222 caregivers and analyzed using descriptive statistics. Results: While 80.6% of caregivers were informed about thalassemia, only 13.1% had prior awareness before their first affected child. Premarital screening was supported by 83.7%, and 64.4% valued genetic counseling. However, 43.7% lacked an understanding of carrier marriage risks. Practices such as parental testing (67.6%) and sibling screening (84.7%) were encouraging. Social stigma (50%) and psychological distress (42.8%) were prevalent, yet mental health support uptake remained low (10.8%). Conclusion: Despite high caregiver engagement, substantial risk perception and psychosocial support gaps persist. Targeted genetic education and counselling are essential for sustainable thalassemia prevention